FUNGSI PEMBAYARAN MAS KAWIN PADA KOMUNITAS KAMPUNG SKOUW SAE, KOTA JAYAPURA (Dowry Payment Function Skouw Sae Community, Jayapura City) - La Usman (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2018)
Residents of the Skouw Sae village, Muara Tami District, Jayapura City often make payments for dowry within and outside the village. The question to be answered regarding the title above is what are the functions of the activity. This study uses an ethno-archeological approach using several techniques, namely: literature study, observation, interview. After all the required data collected is then described, analyzed and interpreted, and drawn a conclusion The results of the study found that there are seven payment functions of dowry. First, to fulfill family food needs. Second, to fulfill reproduction needs for the continuity of individuals, families, clans and communities. Third, to support the payment of compensation from the husband's family to the wife's family in order to meet the comfort and welfare needs of the wife's family. Fourth, for Christmas celebrations and ritual activities at traditional houses, in order to fulfill safety needs. Fifth, fulfillment of family relaxation needs. Sixth, meeting the needs of the movement to bring closer relations between women who are separated from their homes. Seventh, supporting traditional and formal education activities to meet the growth needs of individual families. Abstrak Warga Kampung Skouw Sae, Distrik Muara Tami, Kota Jayapura sering melakukan pembayaran mas kawin dalam maupun luar kampung. Pertanyaan yang ingin dijawab berkaitan dengan judul di atas adalah apa saja fungsi kegiatan tersebut. Penelitian ini menggunakan pendekatan etnoarkeologi dengan menggunakan beberapa teknik yaitu: studi pustaka, observasi, wawancara. Setelah semua data yang dibutuhkan terkumpul kemudian dideskripsikan, dianalisis dan diinterpretasikan, dan ditarik suatu kesimpulan Hasil penelitian menemukan terdapat tujuh fungsi pembayaran mas kawin. Pertama, untuk pemenuhan kebutuhan pangan keluarga. Kedua, untuk pemenuhan kebutuhan reproduksi guna kesinambungan individu, keluarga, klan dan komunitas. Ketiga, untuk mendukung pembayaran ganti rugi dari keluarga suami terhadap keluarga istri guna memenuhi kebutuhan kenyamanan dan kesejahteraan keluarga istri. Keempat, untuk perayaan Natal serta kegiatan ritual pada rumah adat, guna pemenuhan kebutuhan keselamatan. Kelima, pemenuhan kebutuhan relaks keluarga. Keenam, memenuhi kebutuhan gerakan mendekatkan hubungan antara perempuan yang terpisah tempat tinggalnya. Ketujuh, mendukung kegiatan pendidikan tradisional dan formal guna pemenuhan kebutuhan pertumbuhan individu keluarga.